Microcirculatory disturbances in type 2 diabetes: early detection using laser doppler flowmetry for personalized care - Shaienko, Zlatoslava O. (Frontiers in Endocrinology, 2025)
IntroductionType 2 diabetes mellitus (T2DM) is frequently associated with microvascular dysfunction that contributes to the development of complications such as neuropathy, nephropathy, and retinopathy. Early detection of these alterations is essential for effective prevention and personalized care.AimTo evaluate microcirculatory changes in patients with type 2 diabetes using laser Doppler flowmetry (LDF).Materials and methodsThis observational study included 25 individuals: 19 patients with T2DM and 6 healthy controls. Microcirculatory parameters were assessed using LDF, a non-invasive technique for evaluating perfusion in real time. Parameters such as endothelial nitric oxide–dependent activity, neurogenic and myogenic regulation, oxidative metabolism, and nutritive blood flow were measured and analyzed.ResultsPatients with T2DM demonstrated significant microcirculatory disturbances, including reduced endothelial NO-dependent activity, increased sympathetic adrenergic and myogenic activity, and elevated oxidative stress levels. A decreased coefficient of variation and increased nutritive flow suggested a compensatory adaptation of vascular tone regulation. A strong positive correlation was identified between the microcirculation index and regulatory system tension (r = 0.7561; p = 0.0002), indicating systemic vascular strain.ConclusionLDF proved to be an effective tool for the early detection of subclinical microvascular changes in patients with T2DM. These findings support the incorporation of LDF into clinical protocols for individualized risk stratification, early intervention, and treatment monitoring. Further longitudinal studies with larger cohorts are warranted to validate its role in precision diabetology.